The role of cardiovascular magnetic resonance in the evaluation of acute myocarditis and inflammatory cardiomyopathies in clinical practice: a comprehensive review - Ismail, Tevfik F.; Hua, Alina; Plein, Sven; D'Cruz, David; Fernando, Michelle M. A.; Friedrich, Matthias; Zellweger, Michael Johannes; Giorgetti, Assuero; Caobelli, Federico; Haaf, Philip (European heart journal - cardiovascular imaging, 2022)
Inflammatory cardiomyopathy (I-CMP) is defined as myocarditis in association with cardiac dysfunction and/or ventricular remodelling. It is characterized by inflammatory cell infiltration into the myocardium and has heterogeneous infectious and non-infectious aetiologies. A complex interplay of genetic, autoimmune, and environmental factors contributes to the substantial risk of deteriorating cardiac function, acute heart failure, and arrhythmia as well as chronic dilated cardiomyopathy and its sequelae. Multi-parametric cardiovascular magnetic resonance (CMR) imaging is sensitive to many tissue changes that occur during myocardial inflammation, regardless of its aetiology. In this review, we summarize the various aetiologies of I-CMP and illustrate how CMR contributes to non-invasive diagnosis.
Gesehen am 10.01.2023